Financial Feasibility Analysis of the Copra Business in Latompa Village, Maligano Subdistrict, Muna Regency - Vijen Valen Devran; Bahari; Abdi (International journal of technology and education research, 2026)
This research is motivated by the lack of information regarding the financial feasibility level of the copra business operated by the community of Latompa Village, Maligano District, Muna Regency. The purpose of this study is to analyze production costs, revenue, income, and the financial feasibility of the copra business based on the R/C ratio, B/C ratio, and Return on Investment (ROI). This research was conducted in June 2025 using a saturated sampling method (census) involving 34 respondents. Data analysis was carried out using descriptive quantitative methods, including calculations of production costs, revenue, income, and financial feasibility analysis using R/C, B/C, and ROI. The results of the study show that the copra business in Latompa Village is financially feasible. An R/C ratio greater than 1 indicates that revenue exceeds production costs. A positive B/C ratio further confirms that every cost incurred provides economic benefits to the farmers. In addition, the positive ROI value demonstrates the ability of the copra business to generate capital returns and profits for business actors. Therefore, the copra business in Latompa Village is financially profitable and has the potential to be further developed